Energy Poverty Impact on Social Economics in Malaysia - Chin Wan Ling,; Kim Gaik Tay,; Hui Hwang Goh, (International Journal of Integrated Engineering, 2024)
Energy poverty presents a global challenge, impacting not only developing countries but also developed nations. The lack of access to energy in modern living gives rise to various problems, including environmental, health, education, and economic issues. However, the current measurement of energy poverty mostly relies on data analysis with different indicators for each method. In this paper, we propose a model capable of evaluating time series-based causal relationships between each indicator and understanding the significance of their influence on each other. We utilize the ARDL approach and VECM model for our analysis. The results show that there is short run cointegration exists in the ARDL bound test, which is further confirmed by the stability test. Overall, the findings demonstrate a significant bidirectional influence of energy consumption with all indicators, except for education in the case of Malaysia.